The Role of Leadership Role Models for Generation Z in Cirebon City - Dedet Erawati (Green Publisher Indonesia, 2024)
To choose a role model, of course, wisdom is needed. This becomes a serious problem if we relate it to generation Z. The urgency of this research is to look at the role of leadership role models for Gen Z. This research uses a qualitative research method with a phenomenological approach. The results of this research show that cultivating a leadership spirit is influenced by three factors, namely: role models, literacy and family.